ABO AND RH BLOOD GROUPS IN CARDIOVASCULAR DISEASES, FROM IRAN - "D.D. Farhud; M. Aghakhan Mohebb; I. Farhud; H. Khavari - Khorasani " (Tehran University of Medical Sciences, 1992)
ABO and Rh blood groups were studied in a total of 1680 patients with cardiovascular diseases (congenital n=547, valvular n=887 and coronary n=246). Statistical analysis (X2and Woolf's Test) showed significant excess of B/O in mitral valve, aortic valve total valvular diseases and heart diseases generally, also an increase of A/O in myocardial infarction. Significant increase of the frequency of Rh(D) positive individuals, was shown in myocardial infarction and total heart diseases.